1992
DOI: 10.1177/074193259201300303
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Students with Learning Problems in Math to Acquire, Understand, and Apply Basic Math Facts

Abstract: Students with learning problems (i.e., students with learning disabilities or emotional disabilities and those considered at-risk for school failure) are not making acceptable math progress in the nation's schools. Fortunately, instructional practices exist that help these students achieve in math. Ten instructional components that have research support for promoting math achievement are presented. A math curriculum, the Strategic Math Series, which incorporates the research-based teaching practices, is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 36 publications
2
114
0
6
Order By: Relevance
“…What is important is that we use what we know now at the same time that we work to improve our knowledge base in the future so that our children receive the most effective mathematics instruction we can give them. Mason & Good (1993) (MMP, two-group and whole-class teaching) Mercer & Miller (1992) ( …”
Section: Discussionmentioning
confidence: 99%
“…What is important is that we use what we know now at the same time that we work to improve our knowledge base in the future so that our children receive the most effective mathematics instruction we can give them. Mason & Good (1993) (MMP, two-group and whole-class teaching) Mercer & Miller (1992) ( …”
Section: Discussionmentioning
confidence: 99%
“…Researchers show CRA-SI as a beneficial instructional method for teaching students with diverse backgrounds, students with disabilities such as specific learning disabilities, intellectual disabilities, and emotional disabilities as well as students who are at-risk for mathematics failure (Butler, Miller, Crehan, Babbitt & Pierce, 2003;Flores, 2009;Peterson, Mercer, O'Shea, 1988;Maccini & Hughes, 2000;Mercer & Miller, 1992;Morin & Miller, 1998;Strozier, Flores, Shippen, & Hinton, 2012;Witzel, Mercer, & Miller, 2003). Research has shown that CRA-SI is effective in building mathematical fluency with place value, addition and subtraction of numbers, multiplication, regrouping, fractions, integers and algebra (Bulter et al, 2003, Flores, 2010Peterson et al, 1988;Maccini & Hughes, 2000;Mercer & Miller, 1992;Morin & Miller, 1998;Strozier et al, 2012;Witzel et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that CRA-SI is effective in building mathematical fluency with place value, addition and subtraction of numbers, multiplication, regrouping, fractions, integers and algebra (Bulter et al, 2003, Flores, 2010Peterson et al, 1988;Maccini & Hughes, 2000;Mercer & Miller, 1992;Morin & Miller, 1998;Strozier et al, 2012;Witzel et al, 2003). A summary of the research studies chronicled by date is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercer and Miller [19] used ten lessons. The concrete manipulatives were used in Lessons 1-3, the representational phase was used in Lessons 4-6.…”
Section: Concrete-semiconcrete-abstract Modelmentioning
confidence: 99%